Cultural Shifts and Ritual Transformations in Reformation Europe
1 online resource.
Keywords: This volume honors the work of a scholar who has been active in the field of early modern history for over four decades. In that time, Susan Karant-Nunn’s work challenged established orthodoxies, pushed the envelope of historical genres, and opened up new avenues of research and understanding, which came to define the contours of the field itself. Like this rich career, the chapters in this volume cover a broad range of historical genres from social, cultural and art history, to the history of gender, masculinity, and emotion, and range geographically from the Holy Roman Empire, France, and the Netherlands, to Geneva and Austria. Based on a vast array of archival and secondary sources, the contributions open up new horizons of research and commentary on all aspects of early modern life. The contributors are: James Blakeley, Robert J. Christman, Victoria Christman, Amy Nelson Burnett, Pia Cuneo, Ute Lotz-Heumann, Amy Newhouse, Marjorie Elizabeth Plummer, Helmut Puff, Lyndal Roper, Karen E. Spierling, James D. Tracy, Mara R. Wade, David Whitford, and Charles Zika